Reference genes for qRT-PCR normalisation in different tissues, developmental stages, and stress conditions of Hypericum perforatum - Zhou, Wen (PeerJ, 2019)
Hypericum perforatum L. is a widely known medicinal herb used mostly as a remedy for depression because it contains high levels of naphthodianthrones, phloroglucinols, alkaloids, and some other secondary metabolites. Quantitative real-time PCR (qRT-PCR) is an optimized method for the efficient and reliable quantification of gene expression studies. In general, reference genes are used in qRT-PCR analysis because of their known or suspected housekeeping roles. However, their expression level cannot be assumed to remain stable under all possible experimental conditions. Thus, the identification of high quality reference genes is essential for the interpretation of qRT-PCR data. In this study, we investigated the expression of 14 candidate genes, including nine housekeeping genes (HKGs) (ACT2, ACT3, ACT7, CYP1, EF1-α, GAPDH, TUB-α, TUB-β, and UBC2) and five potential candidate genes (GSA, PKS1, PP2A, RPL13, and SAND). Three programs—GeNorm, NormFinder, and BestKeeper—were applied to evaluate the gene expression stability across four different plant tissues, four developmental stages and a set of abiotic stress and hormonal treatments. Integrating all of the algorithms and evaluations revealed that ACT2 and TUB-β were the most stable combination in different developmental stages samples and all of the experimental samples. ACT2, TUB-β, and EF1-α were identified as the three most applicable reference genes in different tissues and stress-treated samples. The majority of the conventional HKGs performed better than the potential reference genes. The obtained results will aid in improving the credibility of the standardization and quantification of transcription levels in future expression studies on H. perforatum.